2018
DOI: 10.1002/er.4295
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a small‐scale compressed air storage (CAS)

Abstract: Summary The use of renewable energy, such as wind and solar, has significantly increased in the last decade. However, these renewable technologies have the limitation of being intermittent; thus, storing energy in the form of compressed air is a promising option. In compressed air energy storage (CAES), the electrical energy from the power network is transformed into a high‐pressure storage system through a compressor. Then, when the demand for electricity is high, the stored high‐pressure air is used to drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…An experimental and theoretical study has been conducted for a high-pressure compressed air tank storage system in which the experimental data was used to assess the wall and air temperatures in the pressurized storage tank of 100 bar. The results showed that the tank wall should be taken into account in the thermal analysis of CAES systems [21]. In another study, a compressed air energy storage is integrated with a biomass-driven power plant with thermal energy storage subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental and theoretical study has been conducted for a high-pressure compressed air tank storage system in which the experimental data was used to assess the wall and air temperatures in the pressurized storage tank of 100 bar. The results showed that the tank wall should be taken into account in the thermal analysis of CAES systems [21]. In another study, a compressed air energy storage is integrated with a biomass-driven power plant with thermal energy storage subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental and theoretical study has been conducted for a high-pressure compressed air tank storage system in which the experimental data was used to assess the wall and air temperatures in the pressurized storage tank of 100 bar. The results showed that the tank wall should be taken into account in the thermal analysis of CAES systems [21]. In another study, a CAES system integrated with a biomass-driven power plant with thermal energy storage was studied and the effects of heat loss in the cavern and the temperature of the soil around the cavern on the performance of the system were investigated [22].…”
Section: Introductionmentioning
confidence: 99%
“…Universities, research centers, and institutions are the starting point of research in renewable energy knowledge and practice. These institutions have carried out several projects on renewable energy sources (RES), like the proposal on compressed air as reserve energy, made at the University of Auckland in New Zealand [6]. Zhou et al [7] and the Ocean University of China (OUC) developed a methodology based on the study of the dynamic characteristics of an actual Offshore Wind Turbines (OWT) in different operational states based on sea tests to determine the negative impact on their structures.…”
Section: Introductionmentioning
confidence: 99%